2017
DOI: 10.1080/08820139.2017.1360338
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of Th17 and Treg Cells in Pulmonary Infections with Gram-Negative Bacteria

Abstract: The aim of this study was to investigate the expression and significance of T helper type 17 (Th17) and regulatory T (Treg) cells in severe pulmonary infection with gram-negative bacteria (GNB). The peripheral venous blood (PVB) and bronchoalveolar lavage fluid (BALF) were collected from patients receiving mechanical ventilation in the intensive care unit (ICU) owing to: (1) pulmonary GNB infection (group I) and (2) nonpulmonary infection (group NI). Patients from the two groups were matched based on their Acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Interestingly, a reduction in T H 17 cells in VAP patients in comparison to ventilated patients who did not develop pneumonia has been reported in one study [16]. Another study found the opposite [15]. While the precise reasons for this discrepancy is unknown, in acute infections and therefore in absence of an adaptive immune response, the numbers of T H cells should not be expected to change.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, a reduction in T H 17 cells in VAP patients in comparison to ventilated patients who did not develop pneumonia has been reported in one study [16]. Another study found the opposite [15]. While the precise reasons for this discrepancy is unknown, in acute infections and therefore in absence of an adaptive immune response, the numbers of T H cells should not be expected to change.…”
Section: Discussionmentioning
confidence: 96%
“…However, published data on IL-17/IL-22 in MV or VAP are conflicting. One study on ventilated patients showed that T H 17 cells were increased both in the peripheral blood and in the lung in VAP patients compared to ventilated patients who did not develop pneumonia [15]. In contrast, another study on ventilated patients showed a reduced number of T H 17 cells in lung lavage fluid of VAP patients compared to those who did not develop VAP, suggesting that T H 17 cells were protective against VAP [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our results also showed that patients who received EEN required a shorter duration of mechanical ventilation and had shorter lengths of ICU stay and hospital stay than those who received DEN, indicating that EEN shortens the duration of mechanical ventilation and the lengths of ICU stay and hospital stay more significantly than DEN; this agrees with the findings of previous studies. 1,2,5 The ET levels in peripheral venous blood were high in both groups before treatment, but they were prominently decreased by enteral nutrition treatment, especially by EEN, indicating that EEN therapy can promote the recovery of gastrointestinal function, stabilize the intestinal flora, and inhibit intestinal flora and ET translocation, which helps to reduce secondary infections in patients with sepsis.…”
Section: Discussionmentioning
confidence: 94%
“…1 Our previous studies showed that there are excessive immune responses such as increased proportions of Th17 cells and Treg cells and decreased Treg/Th17 ratio in patients with sepsis caused by gram-negative bacilli in the lungs. 2 Nutritional therapy has become an important therapeutic measure for patients with sepsis. Enteral nutrition improves intestinal mucosal barrier function, promotes intestinal mucosal repair, and stabilizes intestinal flora.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe pulmonary infections have limited systemic activity and reduced ability to excrete sputum independently, which can result in thick sputum and the accumulation of secretions, and thus increases the risk of airway blockage (10,11). Studies have shown that the treatment of severe pulmonary infections should focus on fighting the infection, removing foreign bodies in the respiratory tract, and ensuring that the respiratory tract is clear of blockages (12).…”
Section: Discussionmentioning
confidence: 99%